The Blue Zones solution [compact disc, unabridged] : eating and living like the world's healthiest people - Buettner, Dan (Blackstone Audio, Inc., 2015)
Dan Buettner lays out a proven plan to maximize your health based on the practices of the world's healthiest people. For the first time, Buettner reveals how to transform your health using smart eating and lifestyle habits gleaned from new research on the diets, eating habits, and lifestyle practices of the communities he's identified as "Blue Zones"--those places with the world's longest-lived, and thus healthiest, people. With this book's audacious belief that the lifestyles of the world's Blue Zones could be adapted and replicated in towns across North America, you'll be inspired by the specific stories of the people, foods, and routines of our healthy elders; understand the role community, family, and naturally healthy habits can play to improve our diet and health; and learn the exact foods--including the fifty superfoods of longevity and dozens of recipes adapted for Western tastes and markets--that offer delicious ways to eat your way to optimum health.